The Analysis Study or Prevalence, Risk Factor, Diagnosis, Management and Complication of Pneumonia: A Comprehensive Systematic Review - Bella Lucinta Rillova Arif Lubis; Dianni Arma Wahyu Setia Ningsih; Dewi Purwanti; Armaita; Linda Marni; Nomira Putri (The Indonesian Journal of General Medicine, 2025)
Introduction: Community-acquired pneumonia (CAP) is a significant global health concern, often leading to severe complications such as bacteremia, respiratory failure, and septic shock. Bacteremia, detected through blood cultures, is a critical indicator of systemic infection and is associated with worse clinical outcomes, including prolonged ICU stays and higher mortality rates. With the rise of antimicrobial resistance and advancements in vaccine research, understanding the current epidemiology and management of CAP, particularly bacteremic CAP, is essential. Methods: This systematic review adheres to PRISMA 2020 guidelines and aims to evaluate the prevalence, risk factors, diagnosis, management, and complications of CAP, with a focus on bacteremia. Studies published between 2019 and 2025 were included, focusing on diagnostic methods, treatment strategies, and outcomes. Data were extracted from PubMed, Embase, Cochrane Library, and Web of Science. Results: Nine studies were included, highlighting trends in diagnostic practices, antibiotic stewardship, and the effectiveness of various treatment regimens. Key findings include increased use of C-reactive protein (CRP) and chest X-rays (CXR) in primary care, the benefits of syndromic molecular testing for pathogen-directed treatment, and the comparative effectiveness of antibiotic regimens such as beta-lactam plus macrolide (BL+M) and fluoroquinolones (FQ). Studies also emphasized the importance of clinical evaluation in interpreting diagnostic results and the need for optimized antibiotic use to reduce complications. Conclusion: This review shows the importance of evidence-based diagnostic and treatment strategies for CAP, particularly in managing bacteremia. While advancements in diagnostics and treatment have improved outcomes, challenges such as antibiotic resistance and underutilization of risk stratification tools remain. Future research should focus on optimizing diagnostic accuracy, treatment efficacy, and antibiotic stewardship to improve patient outcomes.